Major Impact of Classroom Environment in Students’ Learning - Husnul Khatimah (Journal of Education Review Provision, 2021)
The cultural environment provides a pattern of living conditions in accordance with the life patterns of its citizens. Active learning is an alternative that is in line with the new paradigm of learning processes that stimulate, challenge and encourage and motivate student creativity. Types of Classroom environment are Assessment-Centered Environments, Face-to-Face Environment, Online Environment, Learner-Centered Environments, Knowledge-Centered Environments, Face-to-face learning environment and Hybrid learning environment. Students will interact with the environment during the learning process. The environment provides a stimulus to the individual and on the other hand the individual responds to the environment. In the process of interaction, behavior changes can occur in individuals. Behavioral changes that occur can be a positive change and can also be negative. The learning environment in the classroom has an influence on improving student learning outcomes. A good classroom learning environment makes students feel comfortable and motivated when carrying out learning activities